(untitled) (Pain medicine, 2024)
Lumbar spine surgeries are complex procedures often associated with challenges in maintaining hemodynamic stability and controlling intraoperative bleeding, which are crucial for optimizing patient outcomes. Clonidine and dexmedetomidine both are α2-adrenergic agonists with sedative and analgesic properties, known for their potential to attenuate sympathetic responses and stabilize hemodynamics. However, their comparative efficacy in lumbar spine surgeries remains underexplored. METHODOLOGY This study was carried out in 40 patients, ASA grade1 and 2, undergoing lumbar spinal instrumentation requiring laminectomy. The patients were randomly allocated into two groups (20 each) using the computer generated random number table. Group C received 2 µg/kg of clonidine diluted in 10 ml of normal saline, given slowly intravenous infusion over 10 min before induction of general anaesthesia. Group D received 1 µg/kg of dexmedetomidine diluted in 10 ml normal saline, given slow intravenous infusion over 10 minutes before induction of general anaesthesia. Heart rate, systolic, diastolic, and mean arterial pressure were monitored before intubation as the baseline and after intubation, 15, 30, and 60 minutes after starting the surgery, and after extubation. The amount of intraoperative blood loss was estimated based on the volume of blood in the suction bottle and the number of the blood-soaked gauze pads (20 mL for a completely blood-soaked gauze and 50 mL for a completely blood-soaked long gauze). OBSERVATION No statistically significant difference was found on comparing the two drugs in terms of Baseline characteristics, Mean Arterial Pressure and the amount of blood loss. However Dexmedetomidine group had a higher reduction in Heart Rate as compared to the Clonidine Group. CONCLUSION In conclusion, both the alpha2 agonist drugs; intravenous clonidine and dexmedetomidine represent valuable options for achieving stable hemodynamics as well as decreases the intraoperative surgical bleeding in lumbar spine surgeries. Total opioid requirements for intraoperative and rescue analgesia in postoperative period were decreased in both the groups.